The Shelduck population in the Bridgwater Bay moulting area - Eltringham, S K; Boyd, H (Wildfowl, 1960)
Most British Shelduck undertake a moult migration in July to areas on the German North Sea coasts, but in 1951 the existence of a moulting population was discovered in Bridgwater Bay, Somerset. The present paper describes the results of a number of aerial counts of the moulting population during 1959. The first migrants appeared in July but many of these appeared to leave before the end of the month without moulting. There is evidence of a second peak in early August followed by a steady build up in numbers to the seasonal maximum of nearly 3,300 recorded at the beginning of September. The largest number of moulting birds (roughly estimated at 2,700) was found at this time also with a smaller concentration later on in October. It is believed that there were at least two and possibly three waves of immigrants in July, (August) and September. Moulting birds were found during August, September and October with maxima in September and October. It seems probable that the first Shelduck were largely passage birds followed by the moult migrants with the non-breeders preceding the breeding birds. Most of the moulting Shelduck were found between Hinckley Point and Steart. The Shelduck population elsewhere in the Bristol Channel and Severn Estuary did not appear to use Bridgwater Bay as a moulting area. The largest number of young birds was seen in early July, suggesting a rather late breeding season in 1959.